Echocardiogrhphic assessment of the effect of type (2) Diabetes mellitus on cardiac performance - Alwan, Fadia J.; Saleh, Anmar Z.; AL-Najjar, Hassan Y. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Diabetes mellitus (DM) causes damaging effects on the cardiac function; these effects can be observed on the diastolic performance of the heart reflected on the change in transmitral blood velocity, the cardiac wall and septum thickness.Objectives: The present study was to assess the diastolic and systolic cardiac muscle performance for patients with type 2 diabetes mellitus compared with control individuals and to evaluate the index of myocardial performance.Patients and Methods: The study involved 97 patients (35 male and 62 female of average age of 56.2 ±10.755) of type 2 diabetes mellitus (DM), they were investigated for their left ventricle performance and compared with 51 normal individuals “the control group” (20 male and 31 female of average age of 41.4 ± 13.196). Measurements of isovolumetric contraction time IVCT, ejection time ET, ejection fraction EF%, isovolumetric relaxation time IVRT, the early and late peak velocities E and A of transmitral flow, left ventricle diameter in diastole and systole LVIDs, LVIDs, posterior wall thickness PWTd, and Interventricular septum thickness in diastole IVSTd were measured, and index of myocardial performance IMP was calculated.Results: Results reveal differences in these parameters for patients group relative to controls, in IVRT, ET, E, A, E/A, EF%, IMP, LVIDs, PWTd and IVSTd all are strongly significant with p value